2007
DOI: 10.1111/j.1365-2648.2007.04105.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient autonomy in nurse‐led shared care: a review of theoretical and empirical literature

Abstract: Nurses cannot rely exclusively on one model of autonomy to foster patient autonomy. Rather, it requires in-depth knowledge of, and interaction with, patients in the context of each particular nursing encounter because people express their autonomy through particular courses of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
1
40
1
2
Order By: Relevance
“…Our findings reinforce the need to give the nurses time during pre-intervention training to critically reflect on their current provision of patient-centred self-management support [33, 45] and the constructs of true shared decision making based on a patient’s own goals [43, 44]. A change in the way patients present their goals prior to the review would also have to be considered [72]. …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our findings reinforce the need to give the nurses time during pre-intervention training to critically reflect on their current provision of patient-centred self-management support [33, 45] and the constructs of true shared decision making based on a patient’s own goals [43, 44]. A change in the way patients present their goals prior to the review would also have to be considered [72]. …”
Section: Discussionsupporting
confidence: 60%
“…With no single route to optimum shared decision making, remaining flexible in approach and being open to new ideas is critical [72]. …”
Section: Discussionmentioning
confidence: 99%
“…It is easier to increase autonomy for persons with sound cognitive abilities and verbal communication skills, because it is simpler for them to express how they want their assistance performed. This aspect was also pointed out by Meyer et al 43 Moser et al 44 found in their review that the empirical literature on patients' perception of autonomy is sparse. In the present study the interviewees clearly described their perception of autonomy and indicated that they strove to maintain their personal autonomy when receiving assistance.…”
Section: Discussionmentioning
confidence: 88%
“…An overview of theoretical and empirical literature showed that various concepts of autonomy exist and that autonomy in long-term care is difficult to understand (Moser et al 2007). People with diabetes are a good example for studying autonomy because of the high prevalence, complexity (co-morbidity and secondary long-term complications), large care demand, and the amount of responsibility that is placed on the patient.…”
Section: Discussionmentioning
confidence: 99%